Social perceptions of future anxiety among university student - Sifi, Mohamed Miloud; Dechache, Nadia (Journal of Human Sciences, 2023)
This study aims to know the social perceptions of future anxiety among the university student and how they are organized according to the theory of the central nucleus of Abrik, considering that the most worries of him is the future. The result was that the students had negative perceptions about the future, which they expressed in the central core through negative manifestations and the material side. As for the peripheral system, its elements were represented in the formation of a family, self-realization, life requirements, health as well as the material side and migration, in addition to the distinguishing elements and which was represented in positive manifestations, and this explains the extent of the university student’s fear of the future, which is reflected in him negatively and this appears in his behavior and acts.